2019
DOI: 10.15575/ijni.v6i2.4401
|View full text |Cite
|
Sign up to set email alerts
|

Market Structure and Competition Price in Islamic Economics

Abstract: This article will discuss market structure and competition prices in islamic economics. Literature searching is the method used in writing this article. This article found that market in Islam is defined as a means of meeting between seller and buyer, where the buyer came to the market with a demand for goods membewa certain to meet with the seller that brings offers the same goods as well. And the outcome of the meeting will produce an agreement between the seller and the buyer of the price level and the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In terms of the management system, Islamic banking shows a number of interesting aspects because it makes the scheme of equity participation, risk, and profit and loss sharing the basis of its financing (Mulyana, 2018;Permana, 2019;Sudana & Marlina, 2019). All of these schemes have one important aspect, namely that all transactions must be real, not just financial transactions, and all parties involved in the contract must share the risk by using a profit and lost sharing scheme.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of the management system, Islamic banking shows a number of interesting aspects because it makes the scheme of equity participation, risk, and profit and loss sharing the basis of its financing (Mulyana, 2018;Permana, 2019;Sudana & Marlina, 2019). All of these schemes have one important aspect, namely that all transactions must be real, not just financial transactions, and all parties involved in the contract must share the risk by using a profit and lost sharing scheme.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, if the workforce is young, then their motivation and physical condition are still strong so productivity increases. From these data, it can be concluded that the workforce working in the shoe and sandal industry, on average, is young (Mulyana, 2018). So that it will increase the duration of the shoe and sandal home industry business.…”
Section: Technical Feasibility Analysismentioning
confidence: 93%
“…Free market is common structure practiced in Riau. In a free market structure, an economic system where the production, distribution, and pricing of goods or services are determined primarily by the interactions of individuals and businesses in the marketplace, without significant government intervention (Mulyana, 2019). Most apiaries sold their honey at a low, illogical price, and delayed harvest to cover the production cost.…”
Section: The Amount Of Nectar Potency Ofmentioning
confidence: 99%